Numerical and Experimental Determination of the Bore Throughput Controlling the Operation of the Differential Section of a Pneumatic Brake Valve - Marcin Kisiel; Dariusz Szpica; Jarosław Czaban (Applied Sciences)
Purpose: To assess the applicability of computational fluid dynamics (CFDs) in determining the flow parameters of inter-chamber nozzle openings in the differential section of a trailer air brake valve. Methodology: Numerical calculations were performed using SolidWorks Flow Simulation (SW-FS) and Ansys Fluent (A-F) with defined boundaries and initial conditions. The results were validated experimentally using the reservoir method and the lumped method for throughput identification. Results: CFD calculations determined the functional dependence of the mass flow rate on the nozzle diameter for a range of control nozzle bore diameters. The SW-FS 2024 and A-F 2023 software showed a mean difference of 4.66% in the total characteristics. The experimental validation resulted in differences of 6.31% (SW-FS) and 5.79% (A-F) compared to the CFD results. Theoretical contribution: This study fills a research gap in applying CFDs to brake valve performance analyses, providing a foundation for developing more complex numerical models to evaluate individual valve sections. Practical implications: The findings suggest that CFDs can be used to accurately determine the flow parameters of control nozzle orifices, with an average of a 6.05% difference from experimental tests. This approach can potentially streamline the design and optimization process for pneumatic brake valves.